Daughters, Dowries, Deliveries:The Effect of Marital Payments on Fertility Choices in India - Marco Alfano (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
This paper investigates the effect of the differential pecuniary costs of sons and daughters on fertility decisions. The focus is on dowries in India, which increase the economic returns to sons and decrease the returns to daughters. The paper exploits an exogenous shift in the cost of girls relative to boys arising from a revision in anti-dowry law. The reform is found to have attenuated the widely documented positive correlation between daughters and their parents' fertility. The observed patterns can be explained by a simple model of sequential fertility decisions where the gender composition of children determines future dowry payments.
Keywords: O15; J12; J13; 330; Dowry; Fertility; India; Son Preferences